2004
DOI: 10.1086/383083
|View full text |Cite
|
Sign up to set email alerts
|

Thirty‐Five New Pulsating DA White Dwarf Stars

Abstract: We present 35 new pulsating DA (hydrogen atmosphere) white dwarf stars discovered from the Sloan Digital Sky Survey (SDSS) and the Hamburg Quasar Survey (HQS). We have acquired high-speed time series photometry of preselected DA white dwarfs with a prime focus CCD photometer on the 2.1 m telescope at McDonald Observatory over 15 months. We selected these stars on the basis of prior photometric and spectroscopic observations by the SDSS and HQS. For the homogeneous SDSS sample, we achieve a success rate of 80% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
174
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 118 publications
(184 citation statements)
references
References 61 publications
8
174
0
2
Order By: Relevance
“…Employing high signal-tonoise spectra, Bergeron et al (1995Bergeron et al ( , 2004, and Gianninas et al (2005Gianninas et al ( , 2006 have found a pure instability strip for the brightest DAVs. On the other hand, there are about 20 DA stars located within the instability strip, for which pulsations are not detected (Mukadam et al 2004). These stars suffer from a poor determination of their surface parameters.…”
Section: Observations Of Davs: the Purity Of The Instability Stripmentioning
confidence: 99%
“…Employing high signal-tonoise spectra, Bergeron et al (1995Bergeron et al ( , 2004, and Gianninas et al (2005Gianninas et al ( , 2006 have found a pure instability strip for the brightest DAVs. On the other hand, there are about 20 DA stars located within the instability strip, for which pulsations are not detected (Mukadam et al 2004). These stars suffer from a poor determination of their surface parameters.…”
Section: Observations Of Davs: the Purity Of The Instability Stripmentioning
confidence: 99%
“…For compact pulsators, the Sloan Digital Sky Survey has been the tool to find and characterize new white dwarf and subdwarf stars, and led to the discovery of more than 200 new pulsators, mainly DAVs, also called ZZ Cetis (Mukadam et al 2004;Mullally et al 2005;Kepler et al 2005a;Castanheira et al 2006Castanheira et al , 2007, and their modelling (Castanheira & Kepler 2008, 2009Romero et al 2012Romero et al , 2013, but also DBVs Nitta et al (2009) and a few DOVs, also called variable PG 1159 or GW Vir stars (Quirion 2009a;Quirion, Fontaine & Brassard 2009b;Woudt, Warner,& Zietsman 2012;Kepler et al 2014). Two new classes of white dwarf pulsators were found, the DQVs (Montgomery et al 2008;Fontaine et al 2009;Williams et al 2013) and the ELMVs Hermes et al (2013a,b); Van Grootel et al (2012, 2013a; Córsico & Althaus (2014).…”
Section: Compact Oscillatorsmentioning
confidence: 99%
“…For the DAVS, the number known has grown from a pre-SDSS number of about 35 to approximately 150 stars [64,65,66,67,68]. In addition, the number of known DBVs has increased from a pre-SDSS number of 9 to a current value of 18, doubling the sample of DBVs [69].…”
Section: Increased Numbers Of Known Pulsatorsmentioning
confidence: 99%